The study of inorganic scintillating materials; Journal of Physics: Conference Series; Vol. 830 : Energy Fluxes and Radiation Effects 2016 - Dudkin G. N. Gennadiy Nikolaevich; Kuznetsov S. I. Sergey Ivanovich; Padalko V. N. Vladimir Nikolaevich; Syrtanov M. S. Maksim Sergeevich (Radiation physics and chemistry of condensed matter, 2017)
Title screen